Improved electrical performance of MOCVD-grown GaN p-i-n diodes with high-low junction p-layers. (December 2019) - Howell-Clark, Jennifer; Guo, Zhibo; Wetzel, Christian; Chow, T. Paul; Guanxi, Piao; Yano, Yoshiki; Tabuchi, Toshiya; Matsumoto, Koh
Highlights: GaN vertical p-i-n diodes benefit from a high/low Mg doping scheme in the p-layer. A 2 × 10 20 cm −3 / 1 × 10 18 cm −3 Mg-doped double layer replaces a uniform 3 × 10 19 cm −3 . The structure enables significant improvement in ideality and hole carrier injection. Abstract: We report that using a high/low p-type junction anode structure results in improved hole injection over a uniformly-doped p-anode layer in GaN pin junction diodes. Quasi-vertical diodes with a 20 nm thick, magnesium concentration of 2 × 10 20 cm −3 layer on top of a 480 nm thick layer with a magnesium concentration of 10 18 cm −3 show greatly increased forward current density – >100× higher – than those with a 500 nm thick uniformly 3 × 10 19 cm −3 Mg-doped p-layer. Forward knee voltage and ideality factor are reduced by a factor of more than two, and reverse leakage current density is also reduced. Additionally, the specific differential series resistance is reduced significantly. With photoluminescence measurements, we found that these improvements are largely due to improved p-GaN material quality of the high/low junction sample with lower average Mg concentration.